TDCS: a new scheduling framework for real-time multimedia OS. Issue 3 (3rd May 2020) - Hu, Wei; Ma, Tianao; Wang, Yonghao; Xu, Fangfang; Reiss, Joshua
ABSTRACT: The emerging real-time hyper-physical system (CPS), such as autonomous vehicle and live interactive media application, requires time deterministic behaviour. This is challenging to achieve by using the traditional general purpose operating system (GPOS). This paper presents a new design of the real-time operating system (OS) scheduling mechanism called 'time deterministic cyclic scheduling' (TDCS) mainly for live multimedia tasks processing. This new scheduler shares a similar philosophy as classic cyclic execution but with flexibility and dynamic configuration. This hybrid design is based on both time-reserved based cyclic execution and priority-based pre-emptive scheduling for mixed criticality applications. The simulation results show that this scheduling scheme can achieve predictable timing behaviour of task delay and jitter under high CPU utilisation. This shows that the proposed scheme is promising for low latency high-performance multimedia censoring tasks that occur in a periodic manner. GRAPHICAL ABSTRACT: